2022
DOI: 10.1021/acs.orglett.2c02150
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Induced Photocatalyst-Free Radical Trifluoromethylation

Abstract: An attractive, versatile, and operationally simple, visible-light-induced, transition-metal-free, photocatalyst-free, and oxidant-free trifluoromethylation has been demonstrated. Triflic anhydride (Tf 2 O), being inexpensive and readily available, was chosen as the radical trifluoromethyl source. Thianthrene was used as a recyclable Tf 2 O-activating reagent, and a high-yielding and scalable trifluoromethylation reaction was achieved. Density functional theory and mechanistic studies showed that a free radical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 48 publications
(21 reference statements)
1
21
0
Order By: Relevance
“…Considering that the homolytic cleavage of Umemoto's reagent was easy to generate trifluoromethyl radical under visible light irradiation and the preparation of trifluoromethyl thianthrenium salts was a simple one-step synthesis protocol, Zhang, Wang, Xia and co-workers developed a visible-light-induced photocatalyst-free, and oxidant-free radical trifluoromethylation method for the preparation of trifluoromethylated N-heterocycles, alkenes, hydrazones, and arenes with excellent yields, in which inexpensive and readily available Tf 2 O was utilized as a radical CF 3 source, and thianthrene served as cyclable Tf 2 O activating reagent (Scheme 30). [50] DFT and mechanistic studies showed that the reaction was more inclined to undergo direct excitation of thianthrenium salts 101 by purple light. Subsequently, excited thianthrenium salts underwent homolytic CÀ S bond cleavage to generate the CF 3 radical and the thianthrenium radical cation TT + * .…”
Section: Methodsmentioning
confidence: 99%
“…Considering that the homolytic cleavage of Umemoto's reagent was easy to generate trifluoromethyl radical under visible light irradiation and the preparation of trifluoromethyl thianthrenium salts was a simple one-step synthesis protocol, Zhang, Wang, Xia and co-workers developed a visible-light-induced photocatalyst-free, and oxidant-free radical trifluoromethylation method for the preparation of trifluoromethylated N-heterocycles, alkenes, hydrazones, and arenes with excellent yields, in which inexpensive and readily available Tf 2 O was utilized as a radical CF 3 source, and thianthrene served as cyclable Tf 2 O activating reagent (Scheme 30). [50] DFT and mechanistic studies showed that the reaction was more inclined to undergo direct excitation of thianthrenium salts 101 by purple light. Subsequently, excited thianthrenium salts underwent homolytic CÀ S bond cleavage to generate the CF 3 radical and the thianthrenium radical cation TT + * .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a catalyst and oxidant-free trifluoromethylation/cyclization of N-arylacrylamides through visible-light-induced homolysis of thianthrenium salts has also been developed. 14 Despite these impressive advances, the generation of CF 3 radicals through SET reduction using cheap and easily available trifluoromethylating reagents, permitting redox-neutral trifluoromethylation/cyclization of N-arylacrylamides, is rarely reported. 4b,7c,8a Recently, Xiao reported that 4-(difluoroamino)-1-[(trifluoromethyl)sulfonyl]pyridinium triflate (TFSP) is an efficient and stable trifluoromethylation reagent that can be readily prepared from cheap and easily available Tf 2 O and DMAP.…”
Section: Letter Synlettmentioning
confidence: 99%
“…Moreover, a catalyst and oxidant-free trifluoromethylation/cyclization of N -arylacrylamides through visible-light-induced homolysis of thianthrenium salts has also been developed. 14 Despite these impressive advances, the generation of CF 3 radicals through SET reduction using cheap and easily available trifluoromethylating reagents, permitting redox-neutral trifluoromethylation/cyclization of N -arylacrylamides, is rarely reported. 4b 7c 8a…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%
See 1 more Smart Citation
“…To address this question, cost-effective and readily available trifluoroacetic acid (TFA), trifluoroacetic anhydride (TFAA) and triflic anhydride (Tf 2 O) have recently been investigated as trifluoromethylation reagents under diverse catalysis by Zhang, Stephenson, Qing and Ritter, etc. [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%